Studies on Shelf-Life of Some Promising Mango (Mangifera indica L.) Hybrids under Ambient Condition - Karuna, K; Kumar, Mukesh; Mankar, Abhay; Tiwari, Dhiru Kumar; Nirgude , Vishal (Journal of Postharvest Technology, 2014)
Eleven mango hybrids Alfazli, Amrapali, Jawahar, Mahmoodbahar, Mallika,  Neeleshan, Neeludin, Prabhashankar, Ratna, Sabri, Sunder Langra and Langra  were taken as local check to study their shelf life. The PLW and spoilage of  fruit increased with prolongation of storage period, regardless of cultivars. On  termination day of storage (15th day) the minimum PLW (18.65%) and  spoilage (22.36%) was noted in Mallika while highest PLW (34.85%) and  spoilage (58.67%) were obtained in check variety Langra. TSS content in fruits  increased up to 12th day and further extension in storage period it declined in  all the cultivars. On concluding day of experiment (15th day) the maximum  TSS was noted in Mallika (23.02°Brix) while the lowest was obtained  inLangra (18.18°Brix). The titratable acidity and ascorbic acid content in fruits  decreased progressively upto end of the experiment. On 15th day of storage the  maximum titratable acidity was recorded in Mallika (0.346%) while the lowest  was obtained in Sabri (0.132%). The highest ascorbic acid produced by Langra  (92.86 mg/100g juice) while,the lowest ascorbic acid was noticed in  Mahmoodbahar (15.18 mg/100g juice). Total sugar enhanced gradually up to  9th day of storage, except in Mallika which showed increasing trend up to 12th day. On last day of storage the maximum total sugars was noticed in Mallika  (14.98%) however, the lowest was recorded in Langra (11.74%). On 12th day  of storage Mallika was organoleptically rated as excellent. On last day of  storage,Amrapali, Mahmoodbahar, Mallika and Neeludin were fair while rest  of the cultivars were under poor grade quality.The keeping quality of Mallika,  Alfazli, Ratna and Amrapali were better than other hybrids and check variety  Langra.Especially fruits of Mallika can be stored for longer period at ambient  conditions.
Keywords: Shelf-life; Mango; Physiological weight loss Spoilage; ascorbic acid Organoleptic quality